Book Reviews. Issue 2 (1st June 2019) - Mering, Sabine von; Wood, Luke B.; Ziegler, J. Nicholas; Bendix, John; Colla, Marcus; Dilger, Alexander
Abstract : Dolores L. Augustine, Taking on Technocracy: Nuclear Power in Germany, 1945 to the Present (New York: Berghahn Books, 2018) Michael Meng and Adam R. Seipp, Modern Germany in Transatlantic Perspective (New York: Berghahn Books, 2017) Cynthia Miller-Idriss, The Extreme Gone Mainstream: Commercialization and Far Right Youth Culture in Germany (Princeton: Princeton University Press, 2017) Constantin Goschler, ed. Compensation in Practice: The Foundation 'Remembrance, Responsibility and Future' and the Legacy of Forced Labour during the Third Reich (New York: Berghahn Books, 2017) Albert Earle Gurganus, Kurt Eisner: A Modern Life (Rochester: Camden House, 2018) Claudia Sternberg, Kira Gartzou-Katsouyanni, and Kalypso Nicolaïdis, The Greco-German Affair in the Euro Crisis: Mutual Recognition Lost? (London: Palgrave MacMillan, 2018)